Our Library’s Music Collection in the Era of Streaming Services - Virág, Barnabás (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
"Does anyone still listen to CDs?" The presentation aims to introduce the operation of our Music Collection by providing qualitative and quantitative data linked to loans, library visits, online repositories with music content, music programs and workshops. Fundamentally, our Music Collection has a value-preserving function linked to processing, preserving, and presenting the documents of local music life in a spectacular form. Virtual exhibitions based on digitized documents, various databases, and knowledge repositories are good tools for organizing knowledge. People can also be introduced to these contents during library programs (e.g., lectures, sessions, and competitions). Due to the three pillars – knowledge organization, preservation of value, and community building – our Music Collection is a place where people return to listen to music on-site in a comfortable armchair while reading their favourite magazine. Due to the ever-changing world, we must apply innovative approaches, react proactively, and adapt to changes (an example of this could be our Creative Studio). The main purpose of this study is to describe the music-related activities of a particular library (Katona József Library, Kecskemét, Hungary); it is descriptive work and does not aim to compare the data and results with those of other libraries.